The management of druginduced gingival overgrowth - M. Mavrogiannis (journal of clinical periodontology, 2006)
Objectives: This review critically evaluates the different therapies that are available to manage drug-induced overgrowth (DIGO). Material and Methods: This review is based on literature identified using the online databases MEDLINE and PUB MED. It is not a systematic review, but a conventional review of the relevant literature. Results: Patients benefit from a non-surgical approach if this can be delivered before commencement of medication although in many instances this may not be practicable. Systemic antibiotic usage has been evaluated in the management of ciclosporininduced gingival overgrowth. Efficacy appears to be equivocal and long-term use is undesirable. Surgical excision remains the main treatment option especially for patients with severe overgrowth. Few studies have compared different techniques with respect to recurrence rate or post-operative sequelae. Conclusion: DIGO is a common clinical problem that often requires intervention. Non-surgical techniques can limit the occurrence of this unwanted affect, reduce the extent of plaque-induced gingival inflammation and reduce the rate of recurrence. Wherever possible this management strategy should be adopted first. Surgical treatment is often the most reliable option and scalpel gingivectomy remains the treatment of choice. Further investigations are required to develop appropriate management strategies to prevent recurrence of DIGO.